The Influence of Taxes , Intangible Assets, Exchange Rates on Transfer Pricing in Multinational Manufacturing Companies Registered on the IDX 2019-2022 - Intan Febrianti; Alimuddin (MultiTech Publisher, 2024)
This research aims to determine the factors influencing transfer practices in multinational manufacturing companies listed on the Indonesian Stock Exchange in 2019-2022. In this research, the factor used is the bonus mechanism intangible asset tax. This research is quantitative research with secondary data in the form of the company's annual financial reports. The sample was selected using a purposive sampling technique and 40 sample data were obtained. The data analysis technique was using multiple linear analysis with the SPSS 23 program The research results show that intangible assets have a positive effect on transfer pricing, while tax variables have a negative impact on transfer pricing